ANALISIS NILAI PERUSAHAAN BANK UMUM SYARIAH DI INDONESIA - ALFIAN HALID SOFIAN (JURNAL MAKRO MANAJEMEN, 2019)
Company value may reflect the assets owned by a company in the form of securities of one of them in the form of shares. The stock price traded on the stock exchange is an indicator of corporate value. Corporate value is influenced by many factors. This study aims examine the effect csr, profitability, liquidity, leverage and growth for the value of the company.This research is a research using quantitative approach. The population in this study were all companies of Sharia Banks registered in Bank Indonesia, from the population used the total sampling method and the total population of 11 Sharia Commercial Banks became the sample. The data used is secondary data.Data analysis used is path analysis with SPSS 23. The results show that CSR can contribute to corporate value, profitability can not contribute to corporate value, liquidity can contribute to firm value, leverage can contribute to firm value, and growth can not contribute to firm value.